Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1302/0301-620x.80b4.0800631
|View full text |Cite
|
Sign up to set email alerts
|

Pollicisation of the index finger

Abstract: We have reviewed 11 patients with congenital absence of the thumb, treated by pollicisation of the index finger, after follow-up for 20 to 38 years. Seven of the hands also had an associated radial club-hand deformity.Function as assessed by the Percival score was excellent in six, good in three, fair in two and poor in four; three of the poor results were in patients with radial club hand. Ten of the 15 transfers were used as normal thumbs, but in five hands function required trick movements. Of the seven uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The index finger may also be slightly involved, leading to poorer results with the new thumb. There is more stiffness of the index finger in radial deficiency compared to ulnar-sided fingers (Clark et al, 1998;Vekris et al, 2011). Vekris et al (2011) noted that pollicization without prior soft tissue distraction could lead to poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The index finger may also be slightly involved, leading to poorer results with the new thumb. There is more stiffness of the index finger in radial deficiency compared to ulnar-sided fingers (Clark et al, 1998;Vekris et al, 2011). Vekris et al (2011) noted that pollicization without prior soft tissue distraction could lead to poorer outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hand function in terms of grasping, lateral pinching, tip pinching and strength was reported in six studies and further quantified in five of them (Aliu et al, 2008;Bachy et al, 2021;Clark et al, 1998;Tan and Tu, 2013;Va ´zquez Rueda et al, 2001;Vekris et al, 2011). Bachy et al (2021) reported the integration of the new thumb into the hand function.…”
Section: Hand Function and Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Other known long-term complications after pollicization include malrotation, failure to grow, excessive length, and stiffness. 17 41…”
Section: Hypoplastic Thumbmentioning
confidence: 99%
“…Twenty-six patients required an additional surgical procedure for functional deficits; these 34 additional procedures were performed: 19 for poor opposition and 15 for limited extension 80 . Other cited long-term postoperative complications are stiffness, malrotation, excessive length, failure to grow, and less consistent results in the setting of radial longitudinal deficiency 14,81 .…”
Section: Thumb Hypoplasiamentioning
confidence: 99%